Effects of Rashba-spin–orbit coupling on superconducting boron-doped nanocrystalline diamond films: evidence of interfacial triplet superconductivity - Somnath Bhattacharyya; Davie Mtsuko; Christopher Allen; Christopher Coleman (New Journal of Physics, 2020)
Among the many remarkable properties of diamond, the ability to superconduct when heavily doped with boron has attracted much interest in the carbon community. When considering the nanocrystalline boron doped system, the reduced dimensionality and confinement effects have led to several intriguing observations most notably, signatures of a mixed superconducting phase. Here we present ultra-high-resolution transmission electron microscopy imaging of the grain boundary and demonstrate how the complex microstructure leads to enhanced carrier correlations. We observe hallmark features of spin–orbit coupling (SOC) manifested as the weak anti-localization effect. The enhanced SOC is believed to result from a combination of inversion symmetry breaking at the grain boundary interfaces along with antisymmetric confinement potential between grains, inducing a Rashba-type SOC. From a pronounced zero bias peak in the differential conductance, we demonstrate signatures of a triplet component believed to result from spin mixing caused by tunneling of singlet Cooper pairs through such Rashba-SOC grain boundary junctions.